Exploring the farming and waste disposal nexus in the UK: Towards a typology of ’Environmental Criminals’ - Smith, Robert (International Journal of Rural Criminology, 2021)
The farming Industry and rural locations are increasingly being targeted by predatory environmental criminals but as will be demonstrated there is also an insider element to environmental crimes. Such criminal activities pose an environmental challenge and require creative solutions. Indeed, the notion of the farmer as an environmental criminal is a contentious addition to the typology of rural criminals. Traditionally, environmental crime was an overlooked and under researched category of criminology, primarily because 'farmers' as a genre were treated with an elevated level of societal respect in line with their 'idyllic' portrayal. They do not fit accepted social constructs and stereotypes of the urban based criminal fraternity. Consequentially, we heard little of the stereotype of the 'bad' farmer. Recent years have seen a rise in public interest and concern relating to ethical aspects of farming leading to a raising of public awareness. Farmers are no longer immune from criticism, nor prosecution. Using documentary research methods this study reports on several high-profile cases at the nexus and reveals an updated typology of rural environmental crimes and criminals.